2022
DOI: 10.5468/ogs.22146
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy in high-risk endometrial cancer: performance, outcomes, and future avenues

Abstract: Endometrial cancer is the second most common gynecological malignancy worldwide, with an overall favorable prognosis. However, a subgroup of patients has a high risk of recurrence and poor prognosis. This review summarizes recently published articles that examined sentinel lymph node (SLN) biopsy in patients with high-risk endometrial cancer. We focused on the performance and outcomes of SLN biopsy, and examined potential methods for improving the management of this high-risk subset. Few studies have examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…For high-risk patients, SLNB had acceptable diagnostic accuracy and can guide adjuvant chemotherapy and radiotherapy [ 42 , 43 ]. It is suggested that SLNB combined with ProMisE classification in the high-risk group needs more data to support [ 44 ]. Furthermore, attention should be paid to preoperative evaluation for suspicious positive lymph nodes or extrauterine invasion and metastasis as complementary to SLNB in high risk group [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…For high-risk patients, SLNB had acceptable diagnostic accuracy and can guide adjuvant chemotherapy and radiotherapy [ 42 , 43 ]. It is suggested that SLNB combined with ProMisE classification in the high-risk group needs more data to support [ 44 ]. Furthermore, attention should be paid to preoperative evaluation for suspicious positive lymph nodes or extrauterine invasion and metastasis as complementary to SLNB in high risk group [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the RS group, para-aortic lymph node dissection or sentinel lymph node sampling, which is important for staging, was performed more frequently than that in the LS group. This could be due to the Firefly technology of the robotic system ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal cuff dehiscence was defined as a full-thickness opening of the anterior and posterior edges of the vaginal cuff without protruding bowel. The surgical procedures performed, including open and laparoscopic hysterectomies, followed previously described techniques [15][16][17][18][19][20]. To ensure that only patients who developed vaginal cuff dehiscence as a complication of hysterectomy were included in the study (as shown in Figure 2), the medical records of patients who developed dehiscence were thoroughly reviewed.…”
Section: Methodsmentioning
confidence: 99%
“…Vaginal cuff dehiscence was defined as a fullthickness opening of the anterior and posterior edges of the vaginal cuff without protruding bowel. The surgical procedures performed, including open and laparoscopic hysterectomies, followed previously described techniques [15][16][17][18][19][20]. Surgical techniques for hysterectomy vary widely and can impact the incidence of vaginal cuff dehiscence.…”
Section: Methodsmentioning
confidence: 99%